Biophysical and ultrasonographic changes in lichen planus compared with uninvolved skin - Taraneh Yazdanparast, MD; Kamran Yazdani, MD, PhD; Philippe Humbert, MD, PhD; Alireza Khatami, MD; Saman Ahmad Nasrollahi, PharmD, PhD; Hamed Zartab, MD; Leila Izadi Firouzabadi, MD; Alireza Firooz, MD (Wolters Kluwer, 2019)
Background: Lichen planus (LP) is a chronic inflammatory disease of the skin. Currently, noninvasive techniques are used to evaluate biophysical properties of the skin in vivo. Objective: In this study, we aimed to evaluate skin biophysical properties in patients with LP and make a comparison between involved and uninvolved skin to provide a better understanding of the pathogenesis of LP. Methods: The stratum corneum hydration, transepidermal water loss, pH, erythema, melanin, sebum, friction, temperature, elasticity parameters (R0, R2, R5), and thickness and echo-density of the epidermis, dermis, and subepidermal low echogenic band were measured on lesions of classic LP in 21 patients and compared with the average of perilesional and symmetrical uninvolved skin (as control) with a paired t test. Results: Stratum corneum hydration (p = .002), sebum (p = .04), R0 (p = .005), and echo-density of the dermis (p = .005) were significantly lower, but pH (p = .007), melanin content (p < .001), erythema (p < .001), temperature (p = .01), thickness of dermis (p = .02), and subepidermal low echogenic band (p < .001) were significantly higher in LP lesions. Conclusion: An evaluation of its biophysical, biomechanical, and ultrasonographic characteristics showed that the skin is an objective, noninvasive, and quantitative measuring tool that can be used to provide valuable information about skin changes in classic LP. Keywords: Lichen planus, biophysical properties, biomechanical properties, ultrasonography